The Effectiveness of Bougainvillea (Bougainvillea spectabilis willd) Extract on Reducing Blood Glucose in Hypercholesterolaemia White Rats - Muhammad Fakhrul Hardani; Baharuddin Hamzah; Ririen Hardani; Magfirah; Sitti Rahmawati; Purnama Ningsih (Postgraduate, University of Mataram, 2025)
Bougainvillea leaves are often used by the public as a treatment by drinking boiled water, but their use as a blood sugar-lowering agent is not supported by scientific data. The purpose of this study was to determine the effect of reducing blood glucose levels and to determine the dose of extract that is effective in in white rats. The plant's herbal extract was prepared using the reflux method with 90% ethanol solvent. This study uses a laboratory experimental method to compare blood glucose levels in white rats before and after administration of herb extract at doses of 100, 200, and 300 mg/kg BW orally using high-fat feed induction and streptozotocin. Blood glucose levels were measured using a glucometer, and mice were declared positive for diabetes with fasting blood sugar levels above 126 mg/dL. The number of test animals used in this study was 30 mice, divided into 6 groups. A randomized block design was used as the research design. The study's findings revealed that administering Bougainville spectabilis willd herb extract at doses of 100, 200, and 300 mg/kg BW can reduce blood glucose in test animals with an effective dose of 200 mg/kg BW